The effectiveness of exposure and response prevention combined with pharmacotherapy for obsessive-compulsive disorder: A systematic review and meta-analysis - Mao, Lingyun; Hu, Maorong; Luo, Lan; Wu, Yunhong; Lu, Zihang; Zou, Jingzhi (Frontiers in Psychiatry, 2022)
Objective: To systematically evaluate the effectiveness of exposure and response prevention (ERP) combined with medication on obsessive-compulsive disorder (OCD). Methods: PubMed, Web of Science, EBSCO, Cochrane, Embase, and Science Direct databases were searched to include randomized controlled trials of ERP combined with medication for OCD that met the criteria. The Yale Brown Obsessive Compulsive Scale was used as the primary outcome indicator, and Depression scales were used as secondary outcome indicators. An evaluation of bias risk was conducted to identify possible sources of bias based on methodological and clinical factors. Review Manager 5.3 and Stata 16.0 software was used to perform meta-analysis of the extracted data. Results: A total of 21 studies with 1113 patients were included. Meta-analysis showed that ERP combined with medication therapy was significantly better than medication therapy alone including SSRIs, Clomipramine and Risperidone (MD= -6.60, 95%CI: -8.35 to -4.84, P<0.00001), but D-cycloserine drugs do not enhance the effect of ERP intervention in patients with OCD (MD= 0.15, 95%CI: -0.87 to 1.17, P=0.77). There is more significant maintenance by combined treatment method of medication plus ERP than medication treatment alone during the follow-up period (MD=-7.14, 95% CI: -9.17 to -5.10, P<0.00001). DCS drugs did not enhance the effect of ERP intervention on depression in patients with OCD (SMD= -0.08, 95% CI: -0.31 to 0.15, P=0.50). ERP combined with drug improved patients' depression levels significantly better than providing drug alone (SMD= -0.40, 95% CI: -0.68 to -0.11, P=0.006). Conclusion: Patients with OCD have significant improvement in symptoms of obsessive-compulsive disorder and depression when ERP is combined with medication, however, not enough to prove that DCS can enhance ERP effectiveness.